Effect of Music Interventions on Sedation in Children Undergoing Magnetic Resonance Imaging: Clinical Trial - Mathur, Ambika; Kamat, Aarti; Philp, Blythe; Tabb, Jennifer; Thomas, Ronald; Mahajan, Prashant; Caldwell, John; Kamat, Deepak (International Journal of Child Health and Nutrition, 2016)
Background: Although parenteral sedation is often required in MRI studies in children, it is stressful and increases the cost of healthcare. Objectives: We evaluated the impact of music interventions in children receiving parenteral sedation for MRI studies on total number of doses of sedation medications, sedation time, levels of cortisol and cytokines, sedation success, adverse events, parental satisfaction, and cost savings. Methods: We conducted a prospective open unblinded four-arm clinical evaluation of interventions on 471 children 1-12 years of age undergoing MRI and receiving parenteral sedation. Children were assigned to active music therapy (AMT), facilitated music listening (FML), and as comparison another intervention (child life intervention or CLI), or no intervention (NI); measures included number of doses of sedation medications, time of sedation, sedation success, adverse events, parental satisfaction, and salivary levels of the stress hormone cortisol and pro-inflammatory cytokines, before and after intervention. Results: The total number of sedation doses, total sedation time, and levels of salivary cortisol and cytokines did not differ between the four groups. One FMLA choice, Wee Sing Animal Songs, resulted in significant decrease in total sedation time and reduction of associated costs. Conclusions: The use of one type of FML led to decreased total sedation time in children. This is an important finding since FML is an inexpensive non-invasive intervention which could be of significant time and cost saving benefits.